2021
DOI: 10.1177/1073191120986608
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Differentiated Assessment of Narcissism in Forensic Contexts: Validating the Narcissistic Admiration and Rivalry Questionnaire–Short Scale (NARQ-S) in a Forensic Sample

Abstract: Grandiose narcissism is a multidimensional construct consisting of agentic and antagonistic aspects with markedly distinct correlates and consequences. However, this complexity has not been reflected in how grandiose narcissism is measured and investigated in forensic contexts. To provide a more nuanced picture of narcissism in a forensic context, we harnessed the Narcissistic Admiration and Rivalry Concept. More precisely, we investigated the psychometric properties of the Narcissistic Admiration and Rivalry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 95 publications
(220 reference statements)
0
4
0
Order By: Relevance
“…This makes the FFNI-particularly FFNI antagonistic narcissism-a potentially relevant predictor in forensic psychology and criminology (cf. DeLisi, 2019), which is supported by recent evidence showing that antagonism in general (Niemeyer et al, 2022) and antagonistic narcissism specifically (Niemeyer et al, 2021) are highly relevant predictors of criminal behavior.…”
Section: The Ffnimentioning
confidence: 77%
See 1 more Smart Citation
“…This makes the FFNI-particularly FFNI antagonistic narcissism-a potentially relevant predictor in forensic psychology and criminology (cf. DeLisi, 2019), which is supported by recent evidence showing that antagonism in general (Niemeyer et al, 2022) and antagonistic narcissism specifically (Niemeyer et al, 2021) are highly relevant predictors of criminal behavior.…”
Section: The Ffnimentioning
confidence: 77%
“…The impairments associated with grandiose, particularly antagonistic narcissism reflect mainly in externalizing behavior, as we found that antagonistic narcissism was associated with domineering and vindictive interpersonal problems and self-reported aggression, including physical aggression. In the offender sample, antagonistic narcissism and almost all of its facets were significantly elevated, underlining the practical relevance of antagonistic traits with respect to criminal behavior (DeLisi, 2019;Niemeyer et al, 2021Niemeyer et al, , 2022.…”
Section: Nomological Networkmentioning
confidence: 92%
“…This makes the FFNI -particularly FFNI antagonistic narcissism -a potentially relevant predictor in forensic psychology and criminology (cf. DeLisi, 2019), which is supported by recent evidence showing that antagonism in general (Niemeyer, Grosz, Zimmermann, et al, 2021), and antagonistic narcissism specifically (Niemeyer, Grosz, Jallalvand, et al, 2021), are highly relevant predictors of criminal behavior. FFNI vulnerable narcissism, on the contrary, shows associations with experiencing less positive and more negative affect (Jauk & Kaufman, 2018), experiencing shame (Di Sarno et al, 2020), lower authentic and higher hubristic pride (Kaufman & Jauk, 2020), higher attachment anxiety and avoidance (particularly its neurotic aspects; Kaufman et al, 2018;Miller, Gentile, et al, 2013), feelings of social exclusion (Mazinani et al, 2021), a cold-submissive interpersonal style (peaking in the aloof-introverted octant of the interpersonal circumplex; Miller, Gentile, et al, 2013), which can be hypothesized to relate particularly to its neurotic aspects.…”
Section: Nomological Networkmentioning
confidence: 79%
“…The impairments associated with grandiose, particularly antagonistic narcissism reflect mainly in externalizing behavior, as we found that antagonistic narcissism was associated with domineering and vindictive interpersonal problems and self-reported aggression, including physical aggression. In the offender sample, antagonistic narcissism and almost all of its facets were significantly elevated, underlining the practical relevance of antagonistic traits with respect to criminal behavior (DeLisi, 2019;Niemeyer, Grosz, Jallalvand, et al, 2021;Niemeyer, Grosz, Zimmermann, et al, 2021).…”
Section: Nomological Networkmentioning
confidence: 92%